O10 Feasibility of auditing new evidence-based partner notification outcome measures stratified by sexual partnership-type. (16th June 2022) - McMahon, Beth; Buitendam, Erna; Symonds, Merle; Estcourt, Claudia; Saunders, John
Abstract : Introduction: BASHH collaborated with the Limiting Undetected Sexually Transmitted Infections to RedUce Morbidity (LUSTRUM) research team to update PN outcome measures across five stages of the care-cascade (elicitation of partners; establishing contactable partners; notification; testing; treatment) stratified by a new partnership classification (established; occasional; new; one-off, sex-worker). 1 We assessed the feasibility of auditing these measures in services using traditional (casual-regular; Service1) and new (Service2) partnership classifications. Methods: Service1 audited PN outcomes for 40 people with gonorrhoea and Service2 for 120 people with chlamydia, and their five most recent partners. Additionally, in Service1, we attempted to deduce the new partnership typology from the clinical notes. Results: At Service1 it was only possible to reclassify partnership-types for 7% of partners. At Service2 partnership-type using the new partnership classification was recorded for 91% of partners ( table 1 ). Established partners had high levels of engagement across the care-cascade. For occasional partners, 91% were notified but fewer accessed services (48%) and tested (43%). One-off partners had the lowest rates of notification (68%), access (23%) and testing (19%), but the highest chlamydia positivity (89%) of all partnership-types. Discussion: It is feasible to audit the new measures across the care-cascade, stratified by partnership-type when recorded in the patient records. In Service1, where only casual-regular partnership-type was recorded it was not feasible to reclassify according to the new partnership-types. Stratifying PN outcomes by partnership-type illuminates important differences in access and positivity and reinforces why it is key to informing PN strategy for STI control. References: Wayal S, Estcourt C, Mercer C, Saunders J, Low N, McKinnon T, Symonds M, Cassell J. Optimising partner notification outcomes for bacterial sexually transmitted infections: a deliberative process and consensus, United Kingdom, 2019. Euro Surveill 2022;27 (3):pii=2001895. https://doi.org/10.2807/1560-7917.ES.2022.27.3.2001895 Estcourt CS, Flowers P, Cassell JA, et al . Going beyond 'regular and casual': development of a classification of sexual partner types to enhance partner notification for STIs. Sexually Transmitted Infections 2022;98: 108-114.